Academic Service Quality Of Student Loyalty With Student Satisfaction As Intervening Variables In PTS X - Novianto Eko Nugroho (Faculty of Economics and Business, Jenderal Soedirman University, 2019)
The quality of academic services is to refer to academic services provided by education institutions / institutions to students as stakeholders. The quality of best academic services is based on the performance of variety groups of educators, education staff and more over janitors. The purpose of this study was to determine the effect of service quality directly influence student satisfaction and to find out the effect of service quality indirectly affected student loyalty through student satisfaction. This research method uses quantitative methods with explanatory research types. The subjects of this study were S1